2017
DOI: 10.1080/15384101.2017.1376149
|View full text |Cite
|
Sign up to set email alerts
|

Role of PEX5 ubiquitination in maintaining peroxisome dynamics and homeostasis

Abstract: Peroxisomes are essential and dynamic organelles that allow cells to rapidly adapt and cope with changing environments and/or physiological conditions by modulation of both peroxisome biogenesis and turnover. Peroxisome biogenesis involves the assembly of peroxisome membranes and the import of peroxisomal matrix proteins. The latter depends on the receptor, PEX5, which recognizes peroxisomal matrix proteins in the cytosol directly or indirectly, and transports them to the peroxisomal lumen. In this review, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 111 publications
2
43
0
Order By: Relevance
“…We recently revealed an indispensable role of TRIM37 in peroxisome biogenesis and the defective import of peroxisomal matrix proteins in cells depleted of TRIM37 [12]. As peroxisomes are involved in maintaining homeostasis of reactive oxygen species (ROS) [39,40] and recent papers show that oxidative stress modulates TFEB activation and MTORC1 activity via the lysosomal ROS sensor, MCOLN1/TRPML1 (mucolipin 1) [41,42], it seemed plausible that the potential disruption in ROS homeostasis mediates MTORC1 inhibition in TRIM37-deficient cells. To test this, we first examined ROS levels by using the DHR123 and CellRox dyes and found the ROS level in TRIM37 KD cells was comparable to those seen in control cells ( Fig.…”
Section: Trim37 Interacts With Mtor and Rragb And Its Depletion Inhibmentioning
confidence: 99%
“…We recently revealed an indispensable role of TRIM37 in peroxisome biogenesis and the defective import of peroxisomal matrix proteins in cells depleted of TRIM37 [12]. As peroxisomes are involved in maintaining homeostasis of reactive oxygen species (ROS) [39,40] and recent papers show that oxidative stress modulates TFEB activation and MTORC1 activity via the lysosomal ROS sensor, MCOLN1/TRPML1 (mucolipin 1) [41,42], it seemed plausible that the potential disruption in ROS homeostasis mediates MTORC1 inhibition in TRIM37-deficient cells. To test this, we first examined ROS levels by using the DHR123 and CellRox dyes and found the ROS level in TRIM37 KD cells was comparable to those seen in control cells ( Fig.…”
Section: Trim37 Interacts With Mtor and Rragb And Its Depletion Inhibmentioning
confidence: 99%
“…The best established role concerns its requirement for peroxisomal matrix protein import [5]. Functional analysis in yeast and mammalian cells revealed that the AAA complex functions as dislocase for the ubiquitinated PTS1 (peroxisomal targeting signal type 1)-import receptor Pex5, enabling further rounds of PTS1-import [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence and functional role of the different Ub-modifications of Pex5 are conserved from yeast to man. According to the published data from different organisms, the AAA-dependent removal of the unloaded Ub-Pex5 is thought to generate room for newly incoming cargo-bound Pex5 molecules, as the binding capacities at the peroxisomal membrane seem to be limited [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The need for ATP comes only at the next steps, when the machinery is reset, that is, when the receptor is extracted back into the cytosol thus freeing the DTM for another protein import event [55]. This involves (a) monoubiquitination of PEX5 at a conserved cysteine residue located near the N terminus of the protein by the RING peroxins of the DTM [56][57][58], (b) extraction of monoubiquitinated PEX5 into the cytosol by the ATP-dependent mechanoenzymes PEX1 and PEX6, a step that also releases PEX7 from the DTM [51,55,[59][60][61], and, finally, (c) the rapid deubiquitination of Ub-PEX5 in the cytosol [62][63][64].…”
Section: Introductionmentioning
confidence: 99%